2010
DOI: 10.1177/154193121005401951
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Nurses Self-Reported Prospective Memory Tasks: What Must they Remember and What do they Forget?

Abstract: Although a nurse's job is inundated with prospective memory (PM) demands, and studies show that PM failures are a key component of adverse medical events, only one study has examined prospective memory in nursing (Grundgeiger, Sanderson, MacDougall, & Venkatesh, 2009). The purpose of the current study was to complement existing research with self-reports from 25 nurses on the PM tasks they must remember and those they forget. Results revealed that nurses most frequently perform episodic tasks, and these tasks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Better preparing nurses to safely fulfil the task of medication administration in the clinical environment, with increased PM memory in the face of interruptions, could lead to a reduction in errors and concomitant improvements to patient safety [13]. Prospective memory plays an important role in successful task management by nurses [9,10,21]. A nurse's work conditions place heavy demands on PM memory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Better preparing nurses to safely fulfil the task of medication administration in the clinical environment, with increased PM memory in the face of interruptions, could lead to a reduction in errors and concomitant improvements to patient safety [13]. Prospective memory plays an important role in successful task management by nurses [9,10,21]. A nurse's work conditions place heavy demands on PM memory.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, the nurses have many kinds of work to do. Thus, it is very important to help them to improve their ability to handle PM tasks [9,10,21]. One limitation of this study was its cross-sectional nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary coding scheme examines whether reported PM tasks (both those they remember and forget) are event-based or time-based tasks, whether they involve the prospective component of PM or the retrospective component, and the degree to which the reported memory problem could be aided through human factors design. We also intend to classify reported PM tasks using an existing PM taxonomy previously used in aviation (Dimukes & Nowinski, 2007) and healthcare (Fink, Pak, Bass, Johnston, & Battisto, 2010;Grundgeiger, Sanderson, MacDougall, & Venkatesh, 2009) that divides PM tasks into five primary categories: episodic, habitual, atypical, interrupted, and interleaving.…”
Section: Designmentioning
confidence: 99%
“…Where PM has been investigated, researchers have resorted to multiple methods to capture it. Using questionnaires, researchers have shown that ICU staff (Fink, Pak, Bass, Johnston, & Battisto, 2010) and anesthesiologists (Dieckmann, Dyrlov, Reddersen, Rall, & Wehner, 2009) encounter PM-demanding situations and experience PM failures. Field studies have shown that ICU nurses face the same five kinds of PM situations that Dismukes and colleagues identified in the cockpit (Grundgeiger, Sanderson, MacDougall, & Venkatesh, 2009).…”
Section: Prospective Memory Demands In Complex Sociotechnical Systemsmentioning
confidence: 99%